Human leukocyte antigen-haploidentical transplantation for relapsed/refractory acute myeloid leukemia: Better leukemia-free survival with bone marrow than with peripheral blood stem cells in patients ≥55 years of age - Baron, Frédéric; Labopin, Myriam; Tischer, Johanna; Ciceri, Fabio; Raiola, Anna Maria; Blaise, Didier; Sica, Simona; Vydra, Jan; Fanin, Renato; Stölzel, Friedrich; Busca, Alessandro; Diez-Martin, Jose Luis; et al. (American journal of hematology, 2022)
The best stem cell source for T-cell replete human leukocyte antigen (HLA)-haploidentical transplantation with post-transplant cyclophosphamide (PTCy) remains to be determined. In this European Society for Blood and Marrow Transplantation retrospective study, we analyzed the impact of stem cell source on leukemia-free survival (LFS) in adult patients with primary refractory or relapsed acute myeloid leukemia (AML) given grafts from HLA-haploidentical donors with PTCy as graft-versus-host disease (GVHD) prophylaxis. A total of 668 patients (249 bone marrow [BM] and 419 peripheral blood stem cells [PBSC] recipients) met the inclusion criteria. The use of PBSC was associated with a higher incidence of grade II-IV (HR = 1.59, p = .029) and grade III-IV (HR = 2.08, p = .013) acute GVHD. There was a statistical interaction between patient age and the impact of stem cell source for LFS (p < .01). In multivariate Cox models, among patients <55 years, the use of PBSC versus BM resulted in comparable LFS (HR = 0.82, p = .2). In contrast, in patients ≥55 years of age, the use of PBSC versus BM was associated with higher non-relapse mortality (NRM) (HR = 1.7, p = .01), lower LFS (HR = 1.37, p = .026) and lower overall survival (HR = 1.33, p = .044). In conclusions, our data suggest that in patients ≥55 years of age with active AML at HLA-haploidentical transplantation, the use of BM instead of PBSC as stem cell source results in lower NRM and better LFS. In contrast among younger patients, the use of PBSC results in at least a comparable LFS.
Keywords: Transplantation, Haploidentical; HLA Antigens; kmenové buňky z periferní krve; Recurrence; Bone Marrow; příprava pacienta k transplantaci; Retrospective Studies; Peripheral Blood Stem Cells; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; recidiva; lidé; transplantace kostní dřeně; Adult; dospělí; Transplantation Conditioning; haploidentická transplantace; Graft vs Host Disease; akutní myeloidní leukemie; HLA antigeny; Humans; transplantace periferních kmenových buněk; Peripheral Blood Stem Cell Transplantation; Bone Marrow Transplantation; Cyclophosphamide; kostní dřeň; cyklofosfamid; Leukemia, Myeloid, Acute; nemoc štěpu proti hostiteli; retrospektivní studie